International Cooperation and the Reform of Public Procurement Policies - Evenett, Simon J.; Hoekman, Bernard M. (World Bank, Washington, DC, 2012)
The decision not to launch negotiations in the World Trade Organization (WTO) on three of the Singapore Issues in the so-called July 2004 package provides an opportunity to revisit the knowledge base on which proposals for further international collective action may be drawn. This paper examines the available evidence on public procurement practices in developing countries that could be relevant to further multilateral rule making on state purchasing. Although there is considerable agreement on ends (efficient, non-corrupt, and transparent public purchasing systems), little information is available on means and, in particular, on the effective and replicable strategies that developing countries can adopt to improve their public procurement systems. A concerted effort to substantially add to the knowledge base on public procurement reforms in developing countries, through targeted research and international exchange of information on implemented procurement policies and outcomes, is critical to identifying areas where further binding multilateral disciplines may be beneficial.